Insights into the Future of Digital Twin Networks and Social Cyber-Physical Systems. - Jocelyn Jie Wang (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2024)
The emergence of Social Cyber-Physical Systems (SCPS) and Digital Twin Networks (DTNs) signifies a groundbreaking change in our approach to understanding and managing complex systems. This paper delves into future perspectives on SCPS and DTNs, emphasizing emerging trends, technological advancements, and their integration within digital twin ecosystems. We offer a comprehensive overview of SCPS and DTN foundational concepts, review their present applications, and explore the potential effects of these technologies across different fields. Additionally, we outline key research directions and challenges poised to influence the development of digital twin ecosystems.